Fractures within the Irish Canyon-Vermillion Creek area, northeastern Uinta Mountains, northwestern Colorado - Detring, John Peter, author; Erslev, Eric A., advisor; Schutt, Derek L., committee member; Siller, Thomas J., committee member (Colorado State University. Libraries, 2009)
In the northeast Uinta Mountains, fold axes are observed to be consistent with Laramide ENE-WSW shortening and Sevier NW-SE shortening. The structural trends and fracture patterns may be due to the cumulative effects of Laramide and Sevier deformation. This research addresses the timing and mechanisms of fracturing within eastern Uinta Mountains, as well as the controls on post-orogenic fracturing. These results will hopefully aid in testing current regional tectonic models, as well as aid in predictions of fracture permeability in analogous water and hydrocarbon producing, basement-involved orogenic basins worldwide. This study analyzes the kinematic indicators and structural geometries within the extreme northeastern Uinta arch, NW Colorado, USA, to resolve its complex strain history. Fracture systems provide permeability as well as create traps in petroleum reservoirs. An understanding of the orientation and timing of fracture systems can test current tectonic models and allow for predictions of fracture orientation as well as allow for predictions of which fractures are open, closed, and fluid conducting. Systematic fracture data collection, detailed field mapping, kinematic analyses, and a combination of 2D seismic interpretations and cross-section analyses were used to address questions concerning the structural geometry and fracture history within the northeastern Uinta Mountains. Data from geologic mapping, 722 slickensided minor faults, 996 joints and the interpretation of a 2D seismic line were used to determine the fracture history and geometry of the Irish Canyon-Vermillion Creek area. Fracture data were collected at 34 stations in pre- and post-Laramide rocks to obtain average joint orientations and to calculate the ideal σ1 orientations of minor faults. Restoration of 2D structural models, constrained by map and 2D seismic data, were conducted using line length balancing techniques which showed that a significant amount of interlayer slip is necessary for a viable structural interpretation. Fault analyses indicate multidirectional deformation with ENE-WSW and NNE-SSW σ1 orientations. There is a predominance of left-lateral faulting associated with the first stage of deformation and a predominance of right-lateral faulting associated with the second stage of deformation. Evidence for this sequence is the observation of right-lateral faults associated with the NNE-SSW σ1 cross-cutting left-lateral faults associated with the ENE-WSW σ1. Joint measurements are trimodal in distribution, with average strikes of N71E, N1E, and N40W. Abutting relationships suggest that the N71E-striking joints are primary and the N1E-striking joints are secondary. The N40W-striking joint set is only found within the Oligocene Bishop Conglomerate and Miocene Browns Park Formation and their strike parallels regional normal faults. Therefore, this set is likely due to extension during the Miocene to Holocene and post dates Laramide deformation. Folding of the Mancos Shale and back-thrusting of the Browns Park Formation were observed in the northeastern portion of the field area. This deformation is possibly in response to the overlying Browns Park Formation gravitationally sliding down dip along its contact with the Mancos Shale. The tectonic history of the Irish Canyon-Vermillion Creek area is consistent with three stages of deformation. The first stage is characterized by N59E-directed thrusting, conjugate strike-slip faulting, and the N71E-striking joint set. The second stage is characterized by an E-W extension resulting in a system of NNW-directed right-lateral faults, localized NNE-directed transpressional thrust faulting, and the N1E-striking joint set. The third stage is by characterized by NE-SW extension resulting in N52W-striking normal faults and the N40W-striking joint set. The first stage of deformation can be attributed to Laramide compression. The second stage of deformation was probably due to a poorly documented late-Sevier/late-Laramide, or post-Laramide event, or a combination of these events. The third stage of deformation can be attributed to a Miocene to Holocene NE-SW extension.
Zip file contains supplementary map.
Keywords: Uinta Mountains; Irish Canyon-Vermillion Creek; Sevier deformation; Laramide deformation; fault data; fracture systems; kinematic analysis; tectonic models; Colorado